John R. Bowman, Capitalist Collective Action. Competition, Cooperation, and Conflict in the Coal Industry., Cambridge: Cambridge University Press / Paris: Editions de la Maison des Sciences de I'Homme, 1989, 253 s., £ 27.50 (hardback). - Chr. Sidenius, Niels (Politica, 1991)
-